An Initial Investigation of the Potential of Robusta Coffee, Arabica Coffee, and Caffeine in Asthma Treatment through the Evaluation of 5-Lipoxygenase Inhibition Activity - Yuniarta, Tegar Achsendo; Handayani, Rosita (Borneo Journal of Pharmacy, 2024)
Numerous studies have documented the potential of coffee to aid in asthma prevention. Nevertheless, research into how coffee influences asthma management has not been available. One known mechanism by which asthma medications work involves inhibiting 5-lipoxygenase (5-LOX) activity. This study aims to determine the potency of Coffea canephora var. Robusta extract (CRE), Coffea arabica extract (CAE), and caffeine are the primary isolates against 5-LOX activity. Extraction was performed by a reflux procedure using 96% ethanol with a sample-total solvent ratio of 1 : 10, an extraction time of 1 hour, and the extraction was conducted in triplicate. Fractionation was carried out by liquid-liquid partition using a chloroform-water system. Caffeine further purification was performed by the sublimation method, and the inhibition of 5-LOX activity was evaluated using the spectrophotometric method at λ = 234 nm. Apigenin was used as a positive control. From the experiment conducted, the IC50 of the CRE, CAE, caffeine, and apigenin against 5-LOX was 32.2 ± 1.4, 42.1 ± 2.3, 14.3 ± 1.6, and 7.4 ± 1.7 µg/mL, respectively. Continued efforts to isolate bioactive compounds from coffee extract led to the discovery of caffeine, which exhibited a more potent inhibitory effect on 5-LOX. The inhibition of 5-LOX activity by caffeine occurs in a non-competitive manner.